Association for Japanese-Language Teaching (Tokyo ; New York, 1984)
The popular Japanese for Busy People series has been taught by thousands of teachers throughout the world without benefit of a teacher's manual. Now, for those teachers who would like to optimize classroom activities, improve technique, broaden pedagogical opportunities, expand resources, and make the most efficient use of teaching time, the English Teacher's Manual for Japanese for Busy People I is ready to extend a helping hand.
Keywords: Japanese language; Textbooks for foreign speakers,English